2018
DOI: 10.7554/elife.38131
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the mitochondrial proteome of Toxoplasma gondii reveals the presence of a divergent cytochrome c oxidase

Abstract: The mitochondrion of apicomplexan parasites is critical for parasite survival, although the full complement of proteins that localize to this organelle has not been defined. Here we undertake two independent approaches to elucidate the mitochondrial proteome of the apicomplexan Toxoplasma gondii. We identify approximately 400 mitochondrial proteins, many of which lack homologs in the animals that these parasites infect, and most of which are important for parasite growth. We demonstrate that one such protein, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
235
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(269 citation statements)
references
References 80 publications
13
235
8
Order By: Relevance
“…B). The signal obtained by complex IV activity assay corresponds to the size reported for T. gondii complex IV recently (Seidi et al , ) supporting the assay's specificity. To further confirm its identity as complex IV, we performed mass spectrometry analysis of this band which confirmed the complex identity, through confirming the presence of all complex IV components (Table ).…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…B). The signal obtained by complex IV activity assay corresponds to the size reported for T. gondii complex IV recently (Seidi et al , ) supporting the assay's specificity. To further confirm its identity as complex IV, we performed mass spectrometry analysis of this band which confirmed the complex identity, through confirming the presence of all complex IV components (Table ).…”
Section: Resultssupporting
confidence: 86%
“…Mitochondrial targeting predictions were done using MitoProt II (https://ihg.gsf.de/ihg/mitoprot.html) and Predotar (https://urgi.versailles.inra.fr/predotar/). The presence (Yes) or absence (No) of the gene product in the proximity tagging‐based mitochondrial proteome is shown (Seidi et al , ) (No – no mass spectrometry data; No* – mass spectrometry data found but the gene is not included in the final list of 421 genes). The fitness score is based on the whole genome CRISPR/CAS9 screen (Sidik et al , ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations